ISOLATION, CHARACTERIZATION AND SCREENING OF ENZYME PRODUCING BACTERIA FROM DIFFERENT SOIL SAMPLES - MOHAMMAD BADRUD DUZA; S A MASTAN (International Journal of Pharma and Bio Sciences, 2013)
The present study was aimed to isolate, identify and screening of enzyme producing bacteria from soil samples. For this purpose the soil samples were collected from agriculture fields at sangam dairy, Guntur district, fish culture ponds, timber depot soil at rural areas of Bhimavaram, West Godavari district and oil mills at Vijayawada, Krishna district, Andhra Pradesh. A total of seventeen strains of bacteria were isolated from soil samples. Out of them nine isolates have amylase producing activity, eight have protease producing activity, two isolates have cellulose releasing activity and two have lipase producing activity. Among seventeen strains of bacteria 8 isolates belongs to Micrococcus sp., six isolates belongs to Bacillus sp., two belongs to Staphylococcus sp. and one belongs to Streptococcus sp. Further optimization studies and gene 16s RNA studies needed to confirm the strains.